The Effectiveness of Lecture Method in Learning Al-Quran Hadith - Alfi Syahrin (Yayasan Bayt Shufiya Nusantara, 2023)
This study aims to increase the motivation and interest in learning class VIII MTs Al-Washliyah Bangun Purba in learning Al-Qur'an and Hadith by using the lecture method combined with group discussions. The method used in this research is Classroom Action Research (PTK), which was conducted in two cycles. Each cycle consists of four stages, namely planning, action, observation, and reflection. In the first cycle, the teacher applied the lecture method to explain the material, followed by group discussions to improve students' understanding and engagement. In the second cycle, the results of the first cycle reflection were used as the basis for modification and improvement of actions in learning. The results showed that the combination of lecture and group discussion methods was effective in increasing students' motivation and interest in learning the Qur'an and Hadith material.